Effect of Cold Work on Cavitation Resistance of an Austenitic Stainless Steel Coating - Cruz,Juliane Ribeiro da (2016)
Abstract Machining procedures of welding deposits are usual and result on cold work hardened surfaces. The cold work effect on cavitation erosion of an austenitic stainless steel surface is assessed. FeCrMnSiB coatings were processed by PTA on AISI 304 plates. Specimens were grouped as the cold work deformed surface (CWHS) and the undeformed polished surface (UPS) specimens. Top surface and transverse section of coatings were analysed for slip lines and hardness changes by light microscopy and Vickers microhardness measurements. Ultrasonic cavitation tests were conducted in accordance to ASTM G32-10. CWHS specimens exhibited slip lines and hardened surfaces while UPS specimens did not show traces of slip lines and had insignificant changes on microhardness. Cold work prior to cavitation indirectly increased the nominal incubation time and reduced the maximum erosion rate. Cold work increases the duration of the acceleration period postponing the onset of the maximum erosion rate and enhancing cavitation resistance.